Kerajinan Bunga Berbahan Limbah Plastik Ditinjau dari Bentuk, Proporsi dan Warna - Qudriani Rahmadianti Ghassani Putri; Mesra Mesra (Mahesa Research Center, 2022)
One of the creativity developments that can be done by students is the development of creativity by managing plastic waste into crafts, in this case flower crafts from plastic waste. This study aims to determine the application of shapes, proportions and colors in the manufacture of flower crafts made from plastic waste by class VIII students of SMP Negeri 2 Kualuh Selatan. This research was conducted from September to November 2021. This study used a qualitative method with qualitative descriptive data analysis techniques. The total population in this study was 241 works with a total sample of 34 works. The sampling technique uses a purposive sampling technique, namely a sampling technique or data source with certain considerations. The results showed that overall flower crafts made from plastic waste made by students of class VIII Suharto State Junior High School 2 Kualuh Selatan obtained good categories in terms of shape, proportion and color.